From the Epipaleolithic to the Middle Ages. Preliminary Research Results of the “Alebastroviy Zavod Rockshelter” in the Elbrus Region - Golovanova Lyubov V.; Doronichev Vladimir B.; Rezepkin Alexey D.; Doronicheva Ekaterina V.; Palamarchuk Roman S. (Поволжская археология, 2023)
The article reports the preliminary research results of a multilayer site, which comprises the cultural layers dating from the Middle Ages, Kuro-Araks culture, Eneolithic, Neolithic and Epipaleolithic. Of particular interest are the Neolithic layers dating from ca. 8.2 ka BP or 6.300 BC to 7.5–6.7 ka BP or 5.700–4.800 BC. The site shows not only the earliest evidence of the Ceramic Neolithic in the North Caucasus and also provides the authors an opportunity to study the transformation of the Neolithic culture over time. There is no ceramics in the lower layer. Lithic assemblage from this layer is dated to 9.5 ka BP and shows many similarities in the materials of the Epipaleolithic sites of the Elbrus region. A hunter-gatherer camp from the beginning of the Holocene, which existed during the Pereslavl cold stage (ca. 10–9 ka BP), has been preserved in the layer.